Computational basis of SARS-CoV 2 main protease inhibition: an insight from molecular dynamics simulation based findings. Issue 19 (15th November 2022) - Avti, Pramod; Chauhan, Arushi; Shekhar, Nishant; Prajapat, Manisha; Sarma, Phulen; Kaur, Hardeep; Bhattacharyya, Anusuya; Kumar, Subodh; Prakash, Ajay; Sharma, Saurabh; Medhi, Bikash
Abstract: The coronavirus disease 2019 (COVID-19) pandemic is caused by newly discovered severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2). One of the striking targets amongst all the proteins in coronavirus is the main protease (M pro ), as it plays vital biological roles in replication and maturation of the virus, and hence the potential target. The aim of this study is to repurpose the Food and Drug Administration (FDA) approved molecules via computer-aided drug designing against M pro (PDB ID: 6Y2F) of SARS CoV-2 due to its high x-ray resolution of 1.95  Å as compared to other published M pro structures. High Through Virtual Screening (HTVS) of 2456 FDA approved drugs using structure-based docking were analyzed. Molecular Dynamics simulations were performed to check the overall structural stability (RMSD), Cα fluctuations (RMSF) and protein-ligand interactions. Further, trajectory analysis was performed to assess the binding quality by exploiting the protein-residue motion cross correlation (DCCM) and binding free energy (MM/GBSA). Tenofovir, an antiretroviral for HIV-proteases and Terlipressin, a vasoconstrictor show stable RMSD, RMSF, better MM/GBSA with good cross correlation as compared to the Apo and O6K. Moreover, the results show concurrence with Nelfinavir, Lopinavir and Ritonavir which have shown significant inhibition in in vitro studies. Therefore, we conclude that Tenofovir and Terlipresssin might also show protease inhibition but are still open to clinical validation in case of SARS-CoV 2 treatment. Communicated by Ramaswamy H. Sarma